PSXIII-31 Effects of protein levels on guinea pig on growth performance, nitrogen utilization, and nutritional composition of meat by guinea pigs. (7th December 2018) - Araujo, M; Molina, A; Falconi, P; Ponce, C
Abstract: The objective of this study was to evaluate de effects of crude protein level on growth performance, nitrogen utilization, and nutritional composition of meat by guinea pigs. Ninety-one guinea pigs (BW= 499.6 ± 52.9 g) were randomly distributed on 32 pens (2 to 4 animals/pen), creating 8 weighing blocks. Animals were fed during 56 d, 1 of 4 experimental diets containing 15, 16, 17 or 18% crude protein (Source: Soybean meal). Performance variables were recorded on a weekly intervals. At d 50, total fecal samples were collected during 5-d to determine N digstibility. At the end of the feeding period animals were slaughter ans muscle samples were collected to evaluate amino-acid content. Data were analized using the mixed procedures of SAS as completely randomized block design. Performace parameters (i.e. ADG, feed intake and feed efficieny) were not affected by the level of protein (P>0.170). Similarlly, final BW, carcass weight, and dressing percent werenot altered by protein level (P>0.147). Nitrogen intake increased as protein level increased on teh diet (Linear: P=0.035). However, Protein digestibility was not affected by dietary treatment (P=0.149). True Protein and Lysine concentrations on muscle was increased as protein increased on the diet (Linear: P < 0.05). Results form this experiment suggest limited effect of protein level at the range studied on performance and Nutrient digestibility. Increased value of Protein and aminoacid suggested greater accreation of aminoacids by the animal, however, further validation and research are required.